If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 2y = 2 + 5y Solving 12 + 2y = 2 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 12 + 2y + -5y = 2 + 5y + -5y Combine like terms: 2y + -5y = -3y 12 + -3y = 2 + 5y + -5y Combine like terms: 5y + -5y = 0 12 + -3y = 2 + 0 12 + -3y = 2 Add '-12' to each side of the equation. 12 + -12 + -3y = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -3y = 2 + -12 -3y = 2 + -12 Combine like terms: 2 + -12 = -10 -3y = -10 Divide each side by '-3'. y = 3.333333333 Simplifying y = 3.333333333
| 5y^2-21y-54=0 | | -24x^13/6x^4 | | 4/7+9/28 | | (-3u^(5/3))(-5u^(-2/3)) | | (-3u^5/3)(-5u^-2/3) | | X+5/2-8=2x-7/3 | | 2y^2=4+y^2 | | 4x/x-6x=1 | | x^2-9x=x-20 | | 5-8=157-36x | | X^2-5x=120 | | 2c+11=9 | | .50z+0.2=.15z-10.5 | | 9x+25=3x+157 | | 2x+11=-9 | | 4x+13=-52+9x | | y=16x^2+40x+32 | | 2v^2=-7v-5 | | x+3x+x+300=1100 | | 40y+4+60y=2 | | 4+6w=2 | | 2w^2+5w=-3 | | 3x+7=70-60x | | -3(2x+6)=-12 | | 7x-4y=-29 | | 2a+10+5a-2= | | t+8m+4t-4m= | | 8q+10q+14= | | .40y+4+.60y=2 | | 8y+12y+3y= | | 5a+6a-9a= | | 3x-5y=-24 |